THE STUDY OF HADITH IN UYUBUN NAFSI'S BOOK TO UNDERSTAND SELF-CENTERED THINKING ERRORS AND HISTRIONIC PERSONALITY TENDENCIES IN YOUTH MUSLIMS USING SOCIAL MEDIA - Adlina, Atika Ulfia; Zuhurul Fuqohak, Mukhamad Agus; Rahmajati, Erina; Prafitri, Dianing; Fatimah, Hurul Aini (International Prophetic Conference (SWAN) FPQS USIM, 2022)
The majority of social media users in Indonesia are youth. Various posts on social media are produced by youth. Unfortunately, the postings produced by young people including young Muslims are dominated by negative content such as hoaxes, propaganda, dramatizations, hate comments, and fake accounts. That negative content leads their behavior to histrionic personality tendencies. These histrionic personality tendencies are caused by the wrong mindset of youth in understanding the concept of self-centeredness. The concept of being self-centered on histrionic tendencies is more understood as a desire to be recognized and cared for unequally. As a result, young people are not aware of the negative content they have created. In fact, young age is a very productive age and has the potential to be directed to more useful things. To strengthen the alleged error in thinking about the self-centered concept in youth, this researcher refers to the hadiths contained in the book of Uyubun Nafsi. The Uyubun Nafsi Book specifically explains the causes of psychological disorders as well as explains the healing efforts. The results of this study indicate that the fallacy of thinking on the concept of self-centered has implications for the way a person perceives, treats, and uses social media. Certain satisfactions and benefits derived from using social media disproportionately will continue to encourage someone to always fulfill personal desires.